Cisco router handbook - Sackett, George C. (McGraw-Hill, 2000)
Cisco is the biggest name in routers, with 60% market share, and McGraw-Hill is the #1 Cisco publisher. So it's no surprise we've produced the grandaddy of all Cisco references--the most complete configuration guide to Cisco routers, with more than 500 possible configurations defined, analyzed, and described. It supplies the depth of information that network administrators and engineers have been clamoring for. (The Cisco Usenet group currently handles over 600 messages a day on router configuration). An additional 200 tips and techniques for troubleshooting and repair ensure that this invaluable reference will be an instant ongoing demand.